Оформлення креслеників у середовищі solidworks відповідно до національних стандартів україни та міждержавних стандартів - Стукалець, І. Г.; Коробка, С. В.; Скляр, Олександр Григорович; Болтянський, Борис Володимирович; Скляр, Радміла Вікторівна; Stukalets, I.; Korobka, S.; Sklіar, Oleksandr; Boltianskyi, Borys; Sklіar, Radmila (Запоріжжя : ТДАТУ, 2024)
UA: В статті розглянуто можливості системи автоматизованого проєктування SolidWorks, яка містить CAD-, CAE, CAM-модулі та дозволяє виконувати широкий спектр інженерних задач, зокрема оформлення креслеників та створення конструкторської документації. Під час дослідження проблематики стосовно оформлення креслеників у середовищі SolidWorks виявлено, що стандартні шаблони файлів моделей деталей та складанних одиниць, які є в переліку шаблонів моделей SolidWorks, потребують додаткових налаштувань для ефективного використання в інженерній практиці машинобудівного виробництва в плані узгодженості файлів моделей виробів з файлами креслеників цих моделей. Досліджено що, незважаючи на наявність шаблонів креслеників відповідно до стандартів ГОСТ у стандартному переліку шаблонів SolidWorks, такі шаблони не відповідають ані вимогам ГОСТ, ані вимогам національних стандартів України, ані міждержавних стандартів, які чинні в Україні. У статті доведено необхідність у створенні шаблонів моделей деталей і складанних одиниць креслеників та описано послідовність створення шаблонів для оформлення специфікації виробу в SolidWorks відповідно до вимог чинних в Україні стандартів. EN: The article examines the capabilities of the SolidWorks automated design system, which contains CAD, CAE, CAM modules and allows you to perform a wide range of engineering tasks, in particular, drawing drawings and creating design documentation. During the study of issues related to the design of drawings in the SolidWorks environment, it was found that the standard file templates of part models and assembly units, which are in the list of SolidWorks model templates, require additional settings for effective use in the engineering practice of mechanical engineering production in terms of consistency of product model files with drawing files these models. This article describes the procedure for creating a product model properties file for later use when creating 3D models of parts and assemblies. It has been established that an effective tool for creating model properties is the Property Tab Builder utility, which is part of the SolidWorks automated design system package, and is a kind of dialog box designer designed for the user to specify product model properties. The use of this dialog box designer to set the properties of the product model is relevant both for design documentation in the form of drawings and for the so-called «paperless» production technology, which does not involve the creation of drawings, but only the creation of an electronic model of the product. The article investigates that, despite the presence of draftsman templates in accordance with GOST standards in the standard list of SolidWorks templates, such templates do not meet either the requirements of GOST, the requirements of the national standards of Ukraine, or the interstate Ukrainian standards. The article proves the need for creating templates of models of parts and assemblies of drafters and describes the sequence of creating templates for designing product specifications in SolidWorks in accordance with the requirements of the Ukrainian standards. A brief description of the procedure for creating draft formats, tables of the main inscription is provided. In addition, it describes the steps to create a BOM file and a BOM template that are synchronized with product model files and model drawings. All the template files proposed in the article meet the current Ukrainian standards for design documentation.
Design of engineering drawings in solidworks according to national standards of ukraine and interstate standards
Keywords: SolidWorks; Property Tab Builder; ДСТУ; кресленик; конструкторська документація; DSTU; engineering drawing; design documentation